Analysis of Kampung Chicken Marketing in Siborongborong District, North Tapanuli Regency - Nababan, Marta Novita Febriani (Talenta Publisher, 2021)
Siborongborong is the first region that produces the largest kampung chicken with an average population of 83,349 heads.This study aims to identify the characteristics of kampung chicken marketing institutions and marketing channels, analyze marketing margins, farmer's share, profit ratio, and marketing costs for kampung chicken, as well as analyze the marketing efficiency of kampung chicken in Siborongborong. The method used in data collection is snowball sampling, while data collection in this study is primary data and secondary data. Primary data was collected through interviews using questionnaires and direct observation of farmers, middlemen and consumers. While secondary data is obtained from the Central Statistics Agency and other agencies related to research as well as from literature, books, or journals that can be used as references to support primary data during research. The results of this study indicated that two marketing institutions are involved, namely breeders and traders. There are two marketing channels, namely the first channel: farmers - retailers - consumers and the second channel: farmers - collectors/agents - retailers - consumers. Marketing analysis can be seen from several calculations, namely, the margin share where in this analysis channel II (IDR. 21,000) is greater than channel I (IDR. 15,000). Farmer's Share channel 1 (77.09%) is greater than channel II (67.69%). In channel II (3.79) profit ratio is greater than channel I (1.82) and in channel II marketing costs (IDR.7.613/kg/month) is greater than channel I (IDR. 5.304/kg/month). The marketing efficiency of kampung chicken is seen from its marketing efficiency, each channel has been efficient with a value between 0-33%.